Challenges to Successful Community-based Integrated Approach to Dementia: A Qualitative Study. Issue 6 (18th August 2019) - Hirakawa, Yoshihisa; Horie, Kotaro; Chiang, Chifa; Shimizu, Hiroko; Andoh, Hideaki; Aoyama, Atsuko
ABSTRACT: The aim of this study is to identify key challenges to successful community-based integrated team approach to the management of older adults with dementia. A nationwide community-based qualitative research strategy was applied. We purposively recruited 24 health-care providers and 13 family caregivers from selected 8 prefectures among 47 prefectures. Face to face interviews were conducted from May to September 2017. Qualitative content analysis was used to analyze the qualitative data. Ten themes regarding the challenges were emerged: Ignored wishes, Family caregivers' full responsibilities, Encouragement, Practical and easy-to-understand information, Essential skills of dementia diagnosis and assessment, Gratitude by helping others, Difference between being kind and overly-kind, Legal barrier against information sharing, Coordination between volunteers and clients, and Conflict avoidance in multidisciplinary collaboration. The findings highlight the need to provide practical and easy-to-understand information for family caregivers, educate physicians in dementia diagnosis and assessment, share personal dementia care information among health-care providers, promote platforms which aim to match dementia care volunteers with older adults with dementia and their families in need of help, and raise awareness of advance care planning among both older individuals and health-care providers.